LEGAL PLURALISM IN RURAL LAND RESILIENCE: TOWARDS SUSTAINABLE FOOD SECURITY IN INDONESIA - Sinaga, Reny Y.; Barus, Le B. (Journal of Sustainable Development Issues, 2023)
The prevailing Food Law, Sustainable Agricultural Land Law, and Village Law have yet to be effectively implemented, considering that the sustainable fulfilment of the country's food needs can only be optimally achieved based on the diversity of local resources. The Food Law, Sustainable Agricultural Land Law, and Presidential Regulation Number 59 of 2019 have yet to address the consistency in the declining contribution of food crops to GDP from 1990 to 2019 and have not rectified the decrease in agricultural land between 2013-2018. A concept of legal reform has been developed, emphasizing a system or order in land resilience in villages to strengthen sustainable food security in Indonesia. Legal reform of this system or order can prevent and handle all forms of ongoing misuse of agricultural land. The transformation of its universal values begins with enacting public opinions as monitoring and corrective actions originating from the village community itself, filtered through village deliberation institutions, followed by collective decision-making and accountability, resulting in developmental actions from supra-village governments.